Early identification on failure mode of loess landslide: insight from case study and physical model experiment - Li, Ran; He, Jiangkun; Zheng, Han; Zhang, Chenyuan; Zhang, Shuai (Frontiers in Earth Science, 2024)
IntroductionThe Loess Plateau has long been plagued by cascading loess landslides. The rapid identification of these landslides, along with the accurate determination of their failure modes, is essential for conducting precise disaster assessments in the region. Such assessments are critical for minimizing both human casualties and economic losses. However, the lack of reliable reference data for the early identification of landslide failure modes has resulted in limited detection accuracy, complicating the differentiation between various failure modes. Therefore, investigating the deformation and failure characteristics of loess landslides under different failure modes is crucial for providing a scientific foundation for early hazard detection and the accurate assessment of risk profiles.MethodsThis work examines the pre-slip deformation and post-slip damage characteristics of the rotational-sliding Huzhu Landslide and the translational-sliding Zhongzhai Landslide through a combination of field investigations, unmanned aerial vehicle surveys, and remote sensing interpretation. Physical model tests were conducted to simulate the instability and failure processes of both rotational and translational loess landslides. Meanwhile, three-dimensional models and orthophoto graphic images at various stages of the landslides were generated using Contexcapture.ResultsThe initial stages of rotational sliding landslides are marked by the formation of distinct tensile cracks at the trailing edge of the slope and minor uplift at the front. As the uplift at the front progresses and numerous extension fissures develop, the stability of the landslide reduces progressively. Upon reaching instability, the sliding velocity of the sliding mass initially accelerates before decelerating, with majority of the mass remaining on the sliding surface and retaining relatively well structural integrity. At the trailing edge of the landslide, characteristic features such as falling scarps, fractured walls, and sunken grooves can be observed, while the front displays significant bulging phenomena. In contrast, translational sliding landslides are initially characterized by minor tensile cracks at the trailing edge and pronounced deformation at the front. As these tensile cracks propagate, the landslide are prone to sudden instability under external triggering factors. Following the onset of instability, the sliding mass undergoes rapid movement, with only a small part of the mass remaining on the sliding surface.DiscussionLandslides triggered by different factors and occurring under varying water content conditions may exhibit significant differences in their pre-failure behavior and post-failure characteristics. Thus, it is imperative to conduct further research in this field to better understand these complex dynamics.